2023
DOI: 10.1177/21925682221148686
|View full text |Cite
|
Sign up to set email alerts
|

Is High-Dose Tranexamic Safe in Spine Surgery? A Systematic Review and Meta-Analysis

Abstract: Study Design Literature review and meta-analysis. Objectives Single-center series may be underpowered to detect whether high-dose (HD) tranexamic acid (TXA) confers a higher risk of complications. We sought to determine the safety and efficacy of HD TXA as compared to low-dose (LD) or placebo. Methods A systematic literature review was performed to find studies where spine surgery patients were given HD TXA (loading dose ≥30 mg/kg). Complication rates were pooled, and meta-analyses performed on outcomes of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…There was no statistically significant difference for the occurrence of DVT and PE between these drugs. Akosman et al [70] performed a meta-analysis about the safety of high-dose TXA in spinal surgery. Results suggested that high dose of TXA is not associated with an increased risk of complications, including DVT and PE.…”
Section: Discussionmentioning
confidence: 99%
“…There was no statistically significant difference for the occurrence of DVT and PE between these drugs. Akosman et al [70] performed a meta-analysis about the safety of high-dose TXA in spinal surgery. Results suggested that high dose of TXA is not associated with an increased risk of complications, including DVT and PE.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as blood loss can be significant in certain complex spine procedures, the use of hemostatic agents such as transexamic acid and other antifibrinolytic agents has become more common. These agents have the potential to become embolic and may be associated with an increased risk of vascular occlusion if they enter the systemic circulation, although no study has demonstrated a difference in thrombotic rate with tranexamic acid (TXA) [72][73][74].…”
Section: Central Retinal Artery Occlusionmentioning
confidence: 99%
“…36,37 In most studies, administration typically entails a preincision loading dose of 10 to 30 mg/kg followed by an infusion with doses generally ranging from 1 to 3 mg · kg −1 · h −1 , although the literature also demonstrates significant outliers from these parameters. 38 “Low-dose” regimens are described in meta-analyses as less than 15-mg/kg loading dose with 1 mg · kg −1 · h −1 or lower infusion rates, and are effective at reducing blood loss and transfusion requirements. 39 Large meta-analyses have also demonstrated improved efficacy and maintenance of safety with “high-dose” tranexamic acid regimens (greater than 30-mg/kg loading dose or an initial dose in excess of 2,000 mg) without associated increased incidences of thromboembolic phenomena, seizures, or nonbleeding mortality in populations of spine surgery patients as well as general noncardiac surgery patients.…”
Section: Perioperative Patient Blood Managementmentioning
confidence: 99%
“…39 Large meta-analyses have also demonstrated improved efficacy and maintenance of safety with "high-dose" tranexamic acid regimens (greater than 30-mg/kg loading dose or an initial dose in excess of 2,000 mg) without associated increased incidences of thromboembolic phenomena, seizures, or nonbleeding mortality in populations of spine surgery patients as well as general noncardiac surgery patients. [38][39][40] While there is no clear consensus on the optimal dosing of tranexamic acid, one commonly employed and reported regimen for adult patients undergoing open spinal instrumentation of three or more vertebral levels is the administration of a 15-mg/kg intravenous loading dose with an intraoperative infusion of 1 mg • kg −1 • h −1 until surgical closure. 36,37 Blood product transfusion algorithms based on goal-directed therapy with conventional coagulation studies (e.g., prothrombin time, activated partial thromboplastin time, platelet count, fibrinogen concentration, and so forth) can be used to direct blood product administration, but more functional studies of whole blood hemostasis based on viscoelastography may be preferred for complex spinal deformity correction surgeries that incorporate osteotomies and severe angular corrections, and hence significant anticipated blood losses.…”
Section: Perioperative Patient Blood Managementmentioning
confidence: 99%
See 1 more Smart Citation